2009 International Conference on Electrical Engineering and Informatics 2009
DOI: 10.1109/iceei.2009.5254809
|View full text |Cite
|
Sign up to set email alerts
|

Identifying abnormalities in Computed Tomography brain images using symmetrical features

Abstract: This paper proposes an automated method to identify abnormalities by exploiting symmetrical property features in Computed Tomography (CT) brain images. This method consists of two main steps; symmetrical axis detection and rule based abnormalities detection. Based on the principle axis theorem, any tilted intracranial is firstly corrected before symmetrical axis is generated. Then, segmented CT brains intracranial are divided into left half and right half used to produce possible feature vectors. Size (area) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Métodos de segmentación. [21,28] utilizan el método de "ventana deslizante" (sliding window segmentation, en inglés) dentro de encefalogramas, para dividir las señales producidas en épocas y segmentarlas en canales [31,59].…”
Section: Segmentación De Los Datosunclassified
See 2 more Smart Citations
“…Métodos de segmentación. [21,28] utilizan el método de "ventana deslizante" (sliding window segmentation, en inglés) dentro de encefalogramas, para dividir las señales producidas en épocas y segmentarlas en canales [31,59].…”
Section: Segmentación De Los Datosunclassified
“…Tyan et al [36], Balasooriya y Perera [37] usan los métodos de Otsu, filtro anisotrópico, máscara gaussiana, métodos morfológicos (erosión y dilatación) para determinar el área cerebral izquierda o derecha, en la que sucedió la ECV y eliminar ruido de fondo; Haiyan Zhang [70] usa un modelo de contorno geométrico activo mejorado. En imágenes de electroencefalogramas, se captura la duración y el tamaño de la amplitud de las ondas mediante la técnica de ventana deslizante [28,32], la descomposición wavelet [44], el dominio de frecuencias características, transformación de wavelet discreta, la longitud de la transformada de Fourier rápida [21,24,59,71,72,73], y la transformada de ondula discreta de superposición máxima (MODWT) [72]; Ceballos [28] con una RNA multi-layer perceptron crea una matriz de características y patrones del electroencefalograma. Otras técnicas mencionadas en general, para realzar el contraste de la imagen en búsqueda de tumores son: técnicas de media, valores de histograma [44], operaciones morfológicas (dilatación y erosión) [11,25,38,42,62]; curtosis [28,33], matriz de co-ocurrencia de niveles de gris [74,75], desviación estándar, asimetría [57], entropía de Shanon [32], algoritmo Gabor [44], el algoritmo k-means [33]; máscara binaria basada en regiones(max-min) [38], así como diversas técnicas de minería de datos [44].…”
Section: Representación Y Descripción (Extracción Y Selección De Caraunclassified
See 1 more Smart Citation
“…In the classification process, two level classification methods are used to detect brain abnormalities by using characteristics in the intensity and wavelet domain [6]. Meanwhile, Diyana et al identified brain abnormalities by using symmetrical features [7]. Any tilted brain image is rotated correctly before symmetrical axis is determined [7].…”
Section: Proceeding Of the International Conference On Advanced Scienmentioning
confidence: 99%
“…Meanwhile, Diyana et al identified brain abnormalities by using symmetrical features [7]. Any tilted brain image is rotated correctly before symmetrical axis is determined [7]. After that, the area and centroid of the abnormalities are chosen as the features in the rule-based abnormalities detection [7].…”
Section: Proceeding Of the International Conference On Advanced Scienmentioning
confidence: 99%